2014
DOI: 10.2323/jgam.60.123
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing, antibiotic resistance, virulence gene and biofilm formation of different Salmonella enterica serotypes

Abstract: Salmonella enterica isolates representing commonly isolated serotypes in Tunisia were analyzed using genotyping and phenotyping methods. ERIC and ITS-PCR applied to 48 Salmonella spp. isolates revealed the presence of 12 and 10 different profiles, respectively. The distribution of profiles among serotypes demonstrated the presence of strains showing an identical fingerprinting pattern. All Salmonella strains used in this study were positive for the sdiA gene. Three Salmonella isolates belonging to serotypes An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
2
12
0
4
Order By: Relevance
“…This is in contrast to the result found by Kagambega et al, 2013 [18] who found that all Salmonella Typhimurium isolated from slaughtered poultry were Penta-resistant with the same sequence type ST313. Highly multidrug-resistant Salmonella Typhimurium was also reported in chicken by many authors [39,33]. The finding in this study could be explained by the fact that there is an emergence of a new Salmonella Typhimurium clone among poultry species.…”
Section: Discussionsupporting
confidence: 73%
“…This is in contrast to the result found by Kagambega et al, 2013 [18] who found that all Salmonella Typhimurium isolated from slaughtered poultry were Penta-resistant with the same sequence type ST313. Highly multidrug-resistant Salmonella Typhimurium was also reported in chicken by many authors [39,33]. The finding in this study could be explained by the fact that there is an emergence of a new Salmonella Typhimurium clone among poultry species.…”
Section: Discussionsupporting
confidence: 73%
“…In general, owing to the administration of antibiotics to improve growth and prevent diseases in food animals, the augmentation of human salmonellosis started with the emergence of foodborne MDR Salmonella (23,38). The information acquired from various studies could be utilized to develop better strategies to eliminate biofilms in the food chain, and accordingly, reduce Salmonella contamination in animal/food chain.…”
Section: Discussionmentioning
confidence: 99%
“…isolated from food producing animals (CLEMENTE et al 2013;DE JONG et al 2014). Although, S. Gallinarum isolated from chickens in Tunisia, were recently reported to be susceptible to all drugs tested (TURKI et al 2014), other studies about the antimicrobial susceptibility profile of animal host-specific Salmonella serovars are still scarce.…”
Section: Introductionmentioning
confidence: 99%